A modified Ranson score to predict disease severity, organ failure, pancreatic necrosis, and pancreatic infection in patients with acute pancreatitis - Luo, Xiuping; Wang, Jie; Wu, Qing; Peng, Peng; Liao, Guolin; Liang, Chenghai; Yang, Huiying; Huang, Jiean; Qin, Mengbin (Frontiers in Medicine, 2023)
Background: Although there are several scoring systems currently used to predict the severity of acute pancreatitis, each of them has limitations. Determine the accuracy of a modified Ranson score in predicting disease severity and prognosis in patients with acute pancreatitis (AP). Methods: AP patients admitted or transferred to our institution were allocated to a modeling group (n=304) or a validation group (n=192). A modified Ranson score was determined by excluding the fluid sequestration parameter and including the modified Computed Tomography Severity Index (CTSI). The diagnostic performance of the modified Ranson score was compared with the Ranson score, modified CTSI, and Bedside Index of Severity in Acute Pancreatitis (BISAP) score in predicting disease severity, organ failure, pancreatic necrosis and pancreatic infection. Results: The modified Ranson score had significantly better accuracy that the Ranson score in predicting all four outcome measures in the modeling group and in the validation group (all P < 0.05). For the modeling group the modified Ranson score had the best accuracy for predicting disease severity and organ failure, and second-best accuracy for predicting pancreatic necrosis and pancreatic infection. For the verification group, it had the best accuracy for predicting organ failure, second-best accuracy for predicting disease severity and pancreatic necrosis, and third-best accuracy for predicting pancreatic infection. Conclusion: The modified Ranson score provided better accuracy than the Ranson score in predicting disease severity, organ failure, pancreatic necrosis and pancreatic infection. Relative to the other scoring systems, the modified Ranson system was superior in predicting organ failure.